Alterações auditivas no primeiro ano de vida em bebês que passaram por Triagem Auditiva Neonatal - Andrade, Enrisângela Lopes Dutra de (2021)
Introdution: The identification of hearing loss in children is a topic widely discussed in the literature. The diagnostic until the age of three months and the therapeutic intervention started until the age of six months promotes the development of understanding and expression of language. Babies at higher risk for hearing loss are those with factors present at birth or acquired during the first years of life and already established in the literature. Objective: To identify if there are hearing disorders in the first year of life of babies screened at birth. Methodology: The study is descriptive, observational, with data collected from hearing screening at a reference maternity hospital, between 4 months (from October 2018 to January 2019). The data were for all babies who were screened to the program in this period, totaling a sample of 651 medical records. 143 children returned for a second assessment with tympanometry and otoacoustics emissions at 12 months, after active search and regardless of whether they passed or failed the NHS. An adapted questionnaire (PEPPER - Persistent Ear Problems Providing for Referral) was applied to survey risk factors for changes in the functioning of the middle ear. The results were responsible for the descriptive form in tables, using x2 to search for an association between the dependent and independent variables Results: Of the 651 babies screened at the maternity hospital, 618 passed the initial screening moment and 33 failed. 30 returned to the retest, which was previously scheduled for 30 days after the test was discharged and 3 of them did not attend the retest. Of the 30 retests, 26 (78.2%) passed and 4 (12.1%) failed, requiring referral for audiological diagnosis. There was no association between risk factors and the result of NHS. The most common risk factors were: family history of hearing loss, stay in the ICU and use of ototoxic drugs for more than 5 days and phototherapy for more than 5 days. At the request of the researcher 12 months after the screening, 143 babies returned for audiological evaluation. Of these, only 143 attended for a second assessment at 12 months. The variable most associated with attendance was maternal age over 27 years, family income above the minimum wage and level of education from high school. Children who failed tympanometry also failed TEOAE, changing their middle ear. 13 children failed tympanometry, despite the satisfactory result in otoacoustic transfers. But of 99 children who passed the TOAE, 13 failed in tympanometry as well. The variable sleeping position and ear infection reported by the mother were the variables that were most associated with changes in the tests. Of 94 children who passed the NHS, 31 failed the reevaluation. Conclusion: Most babies passed the NHS. The risk factors were not associated with the result of failure. It is of utmost importance to monitor these babies in a pediatric outpatient clinic, as many developed hearing disorders in the first year of life.